PENGENDALIAN PENYAKIT BERCAK COKLAT PADA FASE VEGETATIF TANAMAN TOMAT (Solanum lycopersicum L.) MENGGUNAKAN PESTISIDA NABATI DAUN BINAHONG - Bengu, Ignasia J; Nirmalasari, Viktoria E; Adan, Fransiska Senia; Parman, Egidius; Sudarso, Ruslan Phopin; Liana, Devi (Jurnal Agriovet, 2024)
The disease that causes many losses to tomato plants is brown spot caused by the fungus Alternaria solani. One effort to control brown spot disease is to use vegetable pesticides. The research method used a randomized block design (RAK), namely binahong leaf vegetable pesticide consisting of 5 treatments: P0= no treatment, P1= 15 mL binahong leaf extract + 85 mL water, P2= 30 mL binahong leaf extract + 70 mL water, P3 = 45 mL binahong leaf extract + 55 mL water, and P4 = 60 mL binahong leaf extract + 40 mL water. The treatment was repeated 3 times, so that there were 15 beds. The results of research on the binahong leaf vegetable pesticide in treatment P4 (60 mL binahong leaf extract + 40 mL water) had a significant effect on the parameters of plant height and number of leaves. Meanwhile, treatment P2 (30 mL of binahong leaf extract + 70 mL of water) had a significant effect on the intensity of attacks